Penerapan Algoritma Entropy dan Aras Menentukan Desa Terbaik Di Pemerintah Kabupaten Labuhanbatu - Abdul Karim (KLIK: Kajian Ilmiah Informatika dan Komputer, 2022)
The purpose of this study is to utilize artificial intelligence to analyze in determining the best villages in Labuhanbatu Regency. The research that will be made is to analyze the best village selection model by utilizing data sets sourced from the Community and Village Empowerment Office via the website. By using the Entropy and Level Algorithm as a tool in completing this research. The Entropy Algorithm is an information value that expresses a measure of the impurity of the attributes of a collection of data objects in units of bits. And Levels is a method used for conceptually ranking criteria, thus this method is very suitable in selecting the best villages in Labuhanbatu district. The research process has several stages, namely training and testing to find the results found will be the conclusion of the research.